Present Bias for Monetary and Dietary Rewards: Evidence from Chinese Teenagers - Stephen L. Cheung; Agnieszka Tymula; Xueting Wang (Institute of Labor Economics (IZA), 2020)
Economists model self-control problems through time-inconsistent preferences. Empirical tests of these preferences largely rely on experimental elicitation methods using monetary rewards, with several recent studies failing to find present bias for money. In this paper, we compare estimates of present bias for money with estimates for healthy and unhealthy foods. In a within-subjects longitudinal experiment with 697 low-income Chinese high school students we find strong present bias for both money and food, and that individual measures of present bias are moderately correlated across reward types. Our experimental measures of time preferences over money predict field behaviours better than preferences elicited over foods.
Keywords: C91; D12; D80; D91; 330; self-control; quasi-hyperbolic discounting; present bias; adolescents; food rewards